Ionomers From Kraft Lignin for Renewable Energy Applications - Farzin, Seefat; Johnson, Tyler J.; Chatterjee, Shyambo; Zamani, Ehsan; Dishari, Shudipto K. (Frontiers in Chemistry, 2020)
Converting industrial/agricultural lignin-rich wastes to efficient, cost-effective materials for electrochemical devices (e.g. fuel cells) can aid in both bio- and energy economy. A major limitation of fuel cells is the weak ion conductivity within the ~2-30 nm thick, ion-conducting polymer (ionomer)-based catalyst-binder layer over electrodes. Here, we strategically sulfonated kraft lignin (a by-product of pulp and paper industries) to design ionomers with varied ion exchange capacities (IECs) (LS x; x= IEC) that can potentially overcome this interfacial ion conduction limitation. We measured the ion conductivity, water uptake, ionic domain characteristics, density, and predicted the water mobility/stiffness of Nafion, LS 1.6, and LS 3.1 in sub-micron thick hydrated films. LS 1.6 showed ion conductivity an order of magnitude higher than Nafion and LS 3.1 in films with similar thickness. The ion conductivity of these films was not correlated to their water uptake and IECs. Within the three-dimensional, less dense, branched architecture of LS 1.6 macromolecules, the –SO3H and –OH groups are in close proximity, which likely facilitated the formation of larger ionic domains having highly mobile water molecules. As compared to LS 1.6, LS 3.1 showed a higher glass transition temperature and film stiffness at dry state which sustained during humidification. On the contrary, Nafion stiffened significantly upon humidification. The smaller ionic cluster within stiff LS 3.1 and Nafion films thus led to ion conductivity lower than LS 1.6. Since LS x ionomers (unlike commercial lignosulfonate) are not water-soluble, they are suitable for low-temperature, water-mediated ion conduction in sub-micron thick films.